2021
DOI: 10.2147/rmhp.s302156
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Scheduling Mode and Experience from the Medical Teams in Aiding Hubei Province During the COVID-19 Outbreak: A Systematic Scoping Review of 17 Studies

Abstract: Introduction Due to COVID-19 outbreak, since January 24, 2020, national medical teams from across the country and the armed forces have been dispatched to aid Hubei. The present review was designed to timely summarize the existing frontline information about nursing scheduling mode with special focus on the length of shifts with the aim to contribute to improve the nurses’ job satisfaction and the quality of nursing services. Methods Articles from Jan 2020 to October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Undoubtedly, reasonable scheduling could promote team cooperation and efficiency. A systematic review of 17 studies about nursing scheduling mode confirmed that most of them were in 4‐h shifts (12/17) and fixed‐grouping scheduling (9/17) in COVID‐19 wards (Zhang, Huang et al., 2021). Therefore, it was recommended to conduct fixed‐grouping scheduling, while the nurse leaders should take into account the nurses’ professional background, age, gender, education level and work experience before grouping.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, reasonable scheduling could promote team cooperation and efficiency. A systematic review of 17 studies about nursing scheduling mode confirmed that most of them were in 4‐h shifts (12/17) and fixed‐grouping scheduling (9/17) in COVID‐19 wards (Zhang, Huang et al., 2021). Therefore, it was recommended to conduct fixed‐grouping scheduling, while the nurse leaders should take into account the nurses’ professional background, age, gender, education level and work experience before grouping.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the research results, in order to cope with the arrival of the next peak, we propose the following three suggestions: First of all, the government should give priority to the protection, care and care measures for front-line medical personnel. Second, hospitals need to ease the crisis of nursing staff allocation at the peak of COVID-19, scienti cally arrange nursing shifts [43], reduce the number of night shifts of nurses who are infected, nurses working in COVID-19 wards should rotate regularly [44], provide psychological assistance [35], create a relaxed working environment [45], actively improve the relationship within the team [46], and provide family help, Finally, personal nurses should improve their ability to cope with stress.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the shortage of nurses, a reasonable scheduling could optimize workforce allocation and alleviate the situation of nurse shortage to some extent. When scheduling, workload, working hours, and the number of critically ill patients should be considered (102). Meanwhile, sending medical staff to the worst infection areas was a practicable solution, and a sustainable support echelon should be established.…”
Section: Discussionmentioning
confidence: 99%